The The Effect of Lapbook Media on Grade 1 Students’ Early Reading Skills - Fitriana, Dwi; Nafiah; Susanto, Rudi Umar; Mariati , Pance (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
This study investigates the effect of lapbook media on the early reading skills of grade 1 students. A quasi-experimental design with a nonequivalent control group was applied, involving 50 students divided into an experimental class (n = 26) using lapbook media and a control class (n = 24) using books and PowerPoint. The data were collected through performance tests and analyzed with the Mann-Whitney test due to non-normal distribution. The results show that the experimental class achieved 96.15% mastery compared to 70.83% in the control class, with a significant difference confirmed by statistical testing (p < 0.05). These findings indicate that lapbook media has a strong positive effect on students’ early reading skills. Practically, lapbooks provide an engaging, interactive medium that supports literacy development, offering teachers an effective alternative to conventional instructional tools in elementary education.